Teachers' Subjective Career Success: A View from Gender and Demographic Background - Gita Fitria Romas Ananda; Tri Muji Ingarianti; Devina Andriany (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The present study explores teachers' subjective careers in gender, length of service, and employment status. In order to do this, 320 teachers from the islands of Java and Kalimantan participated in a quantitative descriptive study. The data were collected using the Subjective Career Success Inventory (SCSI) and analyzed using SPSS. The result showed that 232 teachers (72.5%) possessed a moderate level of subjective career success. Gender played a significant role in the recognition and influence dimensions. Recognition, influence, quality work, and meaningful work dimensions were all influenced by the length of employment, while employment status plays a role in recognition, quality work, and influence dimensions. Income level and teaching certificate differ in teachers' subjective career success, particularly the influence dimension. Overall gender, length of service, and employment status all played a role in teachers' subjective career success.